Simulation of industrial 60Со gamma-ray source by Monte-Carlo method - V. I. Gulik (Ядерна фізика та енергетика)
Calculation model developed by means of Monte Carlo code MCNP 4c for 60Со gamma-irradiation source is presented. The simulation of gamma-ray transport in the developed model was carried out. Gamma-ray absorbed doses for different dwell positions were calculated. The distribution of the absorbed dose depending on the location of the material in the cell for irradiation is presented. The use of Monte Carlo simulation for control and verification of gamma-ray irradiation has been recommended for industrial gamma-ray sterilization facilities.